Identification of a RAD52 Inhibitor Inducing Synthetic Lethality in BRCA2-Deficient Cancer Cells - Yang, Qianye; Li, Yu; Sun, Rong; Li, Jian (Frontiers in Pharmacology, 2021)
Breast cancer susceptibility gene 1/2 (BRCA1/2) are frequently mutated in many malignant tumors, such as breast cancer and ovarian cancer. Studies have demonstrated that inhibition of RAD52 gene function in BRCA2 deficient cancer causes synthetic lethality, suggesting a potential application of RAD52 in cancer targeted therapy. Here, we performed a virtual screening by targeting the self-association domain (residues 85-159) of RAD52 with a library of 66,608 compound and found one compound , C791-0064, specifically inhibited the proliferation of BRCA2 deficient cancer cells. Our biochemical and cell based experiments data suggested that C791-0064 specifically bound to RAD52 and disrupted the single strand annealing activity of RAD52. Taken together, C791-0064 is a promising leading compound worthy further exploitation in the context of BRCA-deficient targeted cancer therapy.